Training for videofluoroscopic swallowing analysis: A systematic review. (3rd September 2021) - Edwards, Ann; Froude, Elspeth; Sharpe, Gabriella; Carding, Paul
Abstract: Purpose: To synthesise the available evidence relating to best practice in training videofluoroscopy and barium swallow analysts. Method: The review was conducted according to the PRISMA statement and registered in PROSPERO (CRD42017053744). Data were extracted from nine databases. Studies were included if they described training approaches for clinicians or students of any profession learning to interpret videofluoroscopic (VFSS) or barium swallow studies and were written in English. The methods were heterogeneous and a metanalysis was not possible; a narrative review is presented. Result: Sixteen studies were eligible, including those designed to evaluate the influence of training as well as those that described training as part of validating an assessment tool or method. The quality of the studies was assessed with the Hawker scale and assigned an NHMRC rating. While the evidence was low quality (NHMRC level IV), training consistently improved the accuracy and reliability of clinicians and students conducting VFSS. No studies reported the outcome of training for barium swallow analysis. There was significant variability in the dose, method, and setting of training. Conclusion: To elucidate best practice in VFSS analysis to ensure training is cost effective and results in accurate diagnosticians requires further research.